2008
DOI: 10.1002/mar.20227
|View full text |Cite
|
Sign up to set email alerts
|

Building customer relationships in an electronic age: The role of interactivity of E‐commerce Web sites

Abstract: This study examines the role of perceived interactivity and other marketing tactics in relationship building with customers in the online retail environment by applying a relationship investment model adapted from De Wulf, Odekerken-Schröder, and Iacobucci (2001). A proposed structure model was tested with data collected from an online survey of 571 respondents. In the model, three subdimensions of perceived interactivity and three marketing tactic variables were incorporated as the antecedents of perceived re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
102
2
5

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(114 citation statements)
references
References 52 publications
5
102
2
5
Order By: Relevance
“…Although co-location, facial expression, body language, and speech are not delivered through the online shopping interface, the element of synchronicity can be enhanced through increased download speed. Furthermore, Yoon, Choi, and Sohn (2008) find Web users' perceptions of synchronicity to be associated with perceived relationship investment by e-tailers.…”
Section: Theoretical Framework and Research Hypothesesmentioning
confidence: 95%
“…Although co-location, facial expression, body language, and speech are not delivered through the online shopping interface, the element of synchronicity can be enhanced through increased download speed. Furthermore, Yoon, Choi, and Sohn (2008) find Web users' perceptions of synchronicity to be associated with perceived relationship investment by e-tailers.…”
Section: Theoretical Framework and Research Hypothesesmentioning
confidence: 95%
“…For example, Bennett (1996) found that the customer's perceptions of a seller's relationship building efforts lead to a stronger commitment to the company. The level of perceived relationship investment further influences behavioral loyalty both in offline (De Wulf et al, 2001) and online contexts (Park, 2011;Yoon, Choi, & Sohn, 2008). We therefore propose:…”
Section: Perceived Relationship Investmentmentioning
confidence: 99%
“…Electronic direct mailing (e-DM) is known as an online newsletter or e-mail an organization uses to keep customers informed (Yoon et al, 2008). Electronic direct mailing facilitates the personalization of relationships.…”
Section: Electronic Direct Mailing (E-dm)mentioning
confidence: 99%